A = 2πrh + 2πr^2
dA/dr = 2π(h + r dh/dr + 2r)
2π(h + r dh/dr + 2r) = 0
r dh/dr = -(h+2r)
dh/dr = -h/r - 2
See whether you can massage that into the desired form.
The total surface area of a right circular cylinder of radius r and height h is
A = 2πrh + 2πr^2. Find dh/dr if A has a fixed value. Answer (−2πr^2−A)/2πr^2
2 answers
A = 2 π r h + 2 π r²
A - 2 π r² = 2 π r h
2 π r h = A - 2 π r²
h = ( A - 2 π r² ) / 2 π r =
A / 2 π r - 2 π r² / 2 π r =
A / 2 π r - ( 2 π / 2 π ) r² / r =
A / 2 π r - 1 ∙ r =
A / 2 π r - r =
( A / 2 π ) ∙ 1 / r - r =
( A / 2 π ) ∙ r ⁻¹ - r
h = ( A / 2 π ) ∙ r ⁻¹ - r
dh / dr = ( A / 2 π ) ∙ d ( r ⁻¹ ) / dr - dr / dr =
( A / 2 π ) ∙ ( - 1 ) ( r ⁻¹⁻¹ ) - 1 =
( A / 2 π ) ∙ ( - 1 ) ( r ⁻² ) - 1 =
- ( A / 2 π ) ∙ ( r ⁻² ) - 1 =
- ( A / 2 π ) ∙ 1 / r ² - 1 =
- ( A / 2 π ) / r ² - 1 =
- A / 2 π r ² - 1
dh / dr = - A / 2 π r ² - 1
If you really must write ( - 2 π r ² - A ) / 2 π r ²
then
dh / dr = - A / 2 π r ² - 1 =
- A / 2 π r ² - 2 π r ² / 2 π r ² =
( - A - 2 π r ² ) / 2 π r ² =
( - 2 π r ² - A ) / 2 π r ²
But expression
dh / dr = - A / 2 π r ² - 1
is simpler
A - 2 π r² = 2 π r h
2 π r h = A - 2 π r²
h = ( A - 2 π r² ) / 2 π r =
A / 2 π r - 2 π r² / 2 π r =
A / 2 π r - ( 2 π / 2 π ) r² / r =
A / 2 π r - 1 ∙ r =
A / 2 π r - r =
( A / 2 π ) ∙ 1 / r - r =
( A / 2 π ) ∙ r ⁻¹ - r
h = ( A / 2 π ) ∙ r ⁻¹ - r
dh / dr = ( A / 2 π ) ∙ d ( r ⁻¹ ) / dr - dr / dr =
( A / 2 π ) ∙ ( - 1 ) ( r ⁻¹⁻¹ ) - 1 =
( A / 2 π ) ∙ ( - 1 ) ( r ⁻² ) - 1 =
- ( A / 2 π ) ∙ ( r ⁻² ) - 1 =
- ( A / 2 π ) ∙ 1 / r ² - 1 =
- ( A / 2 π ) / r ² - 1 =
- A / 2 π r ² - 1
dh / dr = - A / 2 π r ² - 1
If you really must write ( - 2 π r ² - A ) / 2 π r ²
then
dh / dr = - A / 2 π r ² - 1 =
- A / 2 π r ² - 2 π r ² / 2 π r ² =
( - A - 2 π r ² ) / 2 π r ² =
( - 2 π r ² - A ) / 2 π r ²
But expression
dh / dr = - A / 2 π r ² - 1
is simpler